2009
DOI: 10.1007/s00520-009-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

Continued success of the rapid response radiotherapy program: a review of 2004–2008

Abstract: The number of patients referred to the RRRP from January 2004-July 2008 remains comparable to our previous report (1996-2003). The overall median interval from referral to consultation for the analysed time period was 4 days. Therefore, we are continuing to meet our goal of providing rapid access to palliative radiation treatment for symptomatic cancer patients. Further information relating to progression and advancements within the clinic aimed at improving our patients' quality of life are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…The present study, which covers August 2008 to June 2012, has revealed further improvement in wait times, with a median wait time of 3 days between referral and consultation. The rrrp also demonstrates 10 . The continued success of the rrrp has influenced the establishment of similar palliative radiation therapy clinics at other cancer centres in Canada and overseas 10,16 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The present study, which covers August 2008 to June 2012, has revealed further improvement in wait times, with a median wait time of 3 days between referral and consultation. The rrrp also demonstrates 10 . The continued success of the rrrp has influenced the establishment of similar palliative radiation therapy clinics at other cancer centres in Canada and overseas 10,16 .…”
Section: Discussionmentioning
confidence: 90%
“…The rrrp also demonstrates 10 . The continued success of the rrrp has influenced the establishment of similar palliative radiation therapy clinics at other cancer centres in Canada and overseas 10,16 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…National and international literature shows a decrease in waiting times for patients to receive palliative radiotherapy when referred to dedicated Rapid Response Palliative clinics 2, 15, 16. However, these clinics do not exist in the majority of Australian and New Zealand radiation centres.…”
Section: Resultsmentioning
confidence: 99%